The Concept Maslahah of Najamuddin al Tufi and It's Relevance of Sharia Business - Munadi Munadi; Budi Iswanto (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2020)
Al-Tufi is one of the maslahah figures. al-Tufi defines maslahah based on two things, in urf and shar'i, while in urf is a factor that leads to goodness and benefits. Like trading that brings profit. While according to shar'i maslahah is a causal factor that leads to the intention of lawmakers in matters of worship, as well as customs. The rationalization effort based on the spirit of shar'i arguments in its dialectical form delivered Al-Tufi's thoughts towards the re-actualization of Islamic law in the field of muamalah which was more applicable and found a significant momentum. Considering the need for renewal of Islamic law based on a public benefit is more pronounced in this modern era especially in business, with this Al-Tufi method, Sharia business law will be dynamic and progressive again. Is not the Islamic Sharia down to earth intending to achieve human maslahah.